2001
DOI: 10.1097/00002030-200102160-00009
|View full text |Cite
|
Sign up to set email alerts
|

Duration of ruptured membranes and vertical transmission of HIV-1: a meta-analysis from 15 prospective cohort studies

Abstract: These results support the importance of duration of ruptured membranes as a risk factor for vertical transmission of HIV and suggest that a diagnosis of AIDS in the mother at the time of delivery may potentiate the effect of duration of ruptured membranes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(16 citation statements)
references
References 25 publications
1
13
0
Order By: Relevance
“…Women with advanced degrees of imunossupression (CD4 < 350 or AIDS) had a significantly higher risk of transmitting HIV to their newborns, similarly to results found in literature [4-7,24]. …”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Women with advanced degrees of imunossupression (CD4 < 350 or AIDS) had a significantly higher risk of transmitting HIV to their newborns, similarly to results found in literature [4-7,24]. …”
Section: Discussionsupporting
confidence: 87%
“…Premature rupture of membranes followed by vaginal delivery was present in one case of newborn infection, confirming it as a collaborating factor for MTCT [24,35]. …”
Section: Discussionmentioning
confidence: 99%
“…One such evidence was unveiled in 2001 by The International Perinatal HIV Group. They showed that, the risk of perinatal HIV transmission increases by 2% with every 1-hour increase in the duration of membrane rupture before delivery in HIV-infected women regardless of whether women receive a mono or combination antiretroviral therapy [15]. Other authorities have, however, raised counter arguments that women infected with HIV might suffer increased morbidity and mortality with Caesarean sections such as delayed wound healing, high fevers, severe anemia, infections and a need for additional surgery [16].…”
Section: Introductionmentioning
confidence: 99%
“…Factors associated with mother-to-child transmission of HIV in the medical literature include high HIV viral load (>1000 copies/mL), rupture of membranes > 4 hours, low CD4 count, chorioamnionitis, instrumentation during delivery and preterm birth (17, 18, 19, 20). …”
Section: Discussionmentioning
confidence: 99%